Mini-FLOTAC, Kato-Katz and McMaster: three methods, one goal; highlights from north Argentina - Barda, Beatrice (2014)
Background: Copro-parasitological diagnosis is still a challenge in management of helminth infections at individualand community levels in resource-limited settings.The aim of our study was to compare the performance of three quantitative techniques: Kato-Katz, McMaster andMini-FLOTAC methids. The study was carried out in Oran, Northern Argentina.Methods: 200 schoolchildren were enrolled to provide a single stool sample, which was tested for helminthinfections with Kato-Katz, McMaster and Mini-FLOTAC methods. The Mini-FLOTAC was performed with two flotationsolutions (FS2 saturated saline and FS7 zinc sulphate). Preparation and reading time for each of the three methodswas calculated both when processing single and multiple samples.Results: Out of 193 schoolchildren examined, 40% were positive for any helminth infection by any method; themost prevalent was Hymenolepis nana (23%) followed by Ascaris lumbricoides (17%) and a third group of lessprevalent helminths: Enterobius vermicularis, Trichuris trichiura and hookworms (11% all together). Mini-FLOTAC FS2was more sensitive than FS7 for H. nana (93% vs 78%) and for other helminths (85% vs 80%), whereas FS7 was moresensitive for A. lumbricoides (87% vs 61%). Kato-Katz method was more sensitive than McMaster method for A.lumbricoides (84% vs 48%) and for other helminths (48% vs 43%) except for H. nana (49% vs 61%). As for eggcounts, Mini-FLOTAC FS2 reported 904 eggs per gram of faeces (EPG) for H. nana (vs 457 with McMaster and 111with Kato-Katz) and 1177 EPG for A. lumbricoides (vs 1315 with Kato-Katz and 995 with McMaster); FS2 detected thehighest EPG for both H.nana and A.lumbricoides (904 vs 568 and 1177 vs 643 respectively), the differences werenot statistically significant. The technique feasibility was calculated: Kato-Katz mean time was 48 minutes/sample,Mini-FLOTAC 13 minutes/sample and McMaster 7 minutes/sample. However, especially for Kato-Katz and Mini-FLOTAC,the mean time (min/sample) decreased significantly when processing multiple samples.Conclusions: Mini-FLOTAC is a promising technique for helminth diagnosis, it is more sensitive than Kato-Katz andMcMaster for H. nana and as sensitive as Kato-Katz and more sensitive than McMaster for A. lumbricoides identification.Egg counts differences although relevant, did not reach statistical significance.